Kinerja Jalan Tingang Kota Palangka Raya dengan Metode Pedoman Kapasitas Jalan Indonesia 2014 - Setiawan, Rizky Wahyu; Elvina, Ina; Supiyan, Supiyan (Jurnal Talenta Sipil, 2024)
Population growth is usually accompanied by an increase in the activities of all communities in an area. Community activities require facilities and infrastructure to support the activities carried out. Transportation is an important activity for the community. Therefore, the existence of a private car is a necessity. Congestion often occurs during peak hours and some of the main roads in Palangka Raya City, such as Tingang Road, experience a significant increase in car traffic. Tingang Road is an important road for the local community because it is an access to residential areas, schools, sub-districts and an alternative road out of the city via Mahir Mahar Road or the outer ring road. The purpose of this study is to analyze and evaluate road performance. This research uses a direct survey method carried out to the field in order to obtain precise information about a condition. After primary and secondary data collection is collected, analysis is carried out using PKJI 2014. Thus, based on the results of the analysis, the performance of the road can be known. The traffic volume is 546.85 skr / hour which occurs during the day, 11:45 to 12:45 WIB. The current capacity is 1667.98 skr/hr. Meanwhile, the degree of saturation is calculated at 0.327, which indicates level of service B, which indicates a good level of road service.